(4, 6‐Dimethyl‐2‐sulfanylidenepyrimidin‐1‐ium) trichlorido(thiourea‐κS)zinc(II). (11th April 2013) - Fu, Wei‐Wei; Chen, Man‐Sheng; Liu, Yang; Zhang, Fu‐Xing
Abstract : The title compound, (C6 H9 N2 S)[ZnCl3 SC(NH2 )2 ], exists as a zincate where the zinc(II) centre is coordinated by three chloride ligands and a thiourea ligand to form the anion. The organic cation adopts the protonated 4, 6‐dimethyl‐2‐sulfanylidenepyrimidin‐1‐ium ( L ) form of 4, 6‐dimethylpyrimidine‐2(1 H )‐thione. Two short N—H...Cl hydrogen bonds involving the pyrimidine H atoms and the [ZnCl3 L ] − anion form a crystallographically centrosymmetric dimeric unit consisting of two anions and two cations. The packing structure is completed by longer‐range hydrogen bonds donated by the thiourea NH2 groups to chloride ligand hydrogen‐bond acceptors.